Coronary artery hypoxic vasorelaxation is augmented by perivascular adipose tissue through a mechanism involving hydrogen sulfide and cystathionine-β-synthase - Donovan, J.; Wong, P.S.; Garle, M.J.; Alexander, S.P.H.; Dunn, W.R.; Ralevic, V. (Wiley, 2018)
Aim: Hypoxia causes vasodilatation of coronary arteries which protects the heart from ischaemic damage through mechanisms including the generation of hydrogen sulfide (H2S), but the influence of the perivascular adipose tissue (PVAT) and myocardium is incompletely understood. This study aimed to determine whether PVAT and the myocardium modulate the coronary artery hypoxic response, and whether this involves hydrogen sulfide. Methods: Porcine left circumflex coronary arteries were prepared as cleaned segments and with PVAT intact, myocardium intact or both PVAT and myocardium intact, and contractility investigated using isometric recording. Immunoblotting was used to measure levels of H2S synthesizing enzymes: cystathionine‐β‐synthase (CBS), cystathionine γ‐lyase (CSE) and 3‐mercaptopyruvate sulfurtransferase (MPST). Results: All three H2S synthesizing enzymes were detected in the artery and myocardium, but only CBS and MPST were detected in PVAT. Hypoxia elicited a biphasic response in cleaned artery segments consisting of transient contraction followed by prolonged relaxation. In arteries with PVAT intact hypoxic contraction was attenuated and relaxation augmented. In arteries with myocardium intact hypoxic contraction was attenuated, but relaxation was unaffected. In replacement experiments, replacement of dissected PVAT and myocardium attenuated artery contraction and augmented relaxation to hypoxia, mimicking in situ PVAT and indicating involvement of a diffusible factor(s). In arteries with intact PVAT, augmentation of hypoxic relaxation was reversed by amino‐oxyacetate (CBS inhibitor), but not DL‐propargylglycine (CSE inhibitor) or aspartate (inhibits MPST pathway). Conclusion: PVAT augments hypoxic relaxation of coronary arteries through a mechanism involving H2S and CBS, pointing to an important role in regulation of coronary blood flow during hypoxia